Ionic Functionalization of Multivariate Covalent Organic Frameworks to Achieve an Exceptionally High Iodine‐Capture Capacity. Issue 41 (7th September 2021) - Xie, Yaqiang; Pan, Tingting; Lei, Qiong; Chen, Cailing; Dong, Xinglong; Yuan, Youyou; Shen, Jie; Cai, Yichen; Zhou, Chunhui; Pinnau, Ingo; Han, Yu
Abstract: Adsorption‐based iodine (I2 ) capture has great potential for the treatment of radioactive nuclear waste. In this study, we apply a "multivariate" synthetic strategy to construct ionic covalent organic frameworks (iCOFs) with a large surface area, high pore volume, and abundant binding sites for I2 capture. The optimized material iCOF‐AB‐50 exhibits a static I2 uptake capacity of 10.21 g g −1 at 75 °C and a dynamic uptake capacity of 2.79 g g −1 at ≈400 ppm I2 and 25 °C, far exceeding the performances of previously reported adsorbents under similar conditions. iCOF‐AB‐50 also exhibits fast adsorption kinetics, good moisture tolerance, and full reusability. The promoting effect of ionic groups on I2 adsorption has been elucidated by experimentally identifying the iodine species adsorbed at different sites and calculating their binding energies. This work demonstrates the essential role of balancing the textural properties and binding sites of the adsorbent in achieving a high I2 capture performance. Abstract : Multivariate covalent organic frameworks provide an ideal platform for ionic functionalization, enabling the integration of large surface areas, high pore volumes, and abundant binding sites, thereby leading to unprecedented levels of I2 ‐capture performance under both static and dynamic adsorption conditions.